2017
DOI: 10.1039/c7ra05601j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and properties of imidazolium-based energetic ionic liquids

Abstract: Energetic ionic liquids bearing a wide liquid temperature range were easily synthesized, which display good thermal stabilities and energetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…To unravel the links between the idealistic situation of an ion pair or a small cluster and the real crystalline material at room temperature, the DFT calculations were compared with experimental data from the solid. For this purpose, the geometries of the ion pair and its dimer were deduced from Single Crystal X‐ray diffraction (SCXRD) measurements reported on the Cambridge Crystallographic Data Centre (CCDC, entry number 1550837) . Table compares selected geometric parameters obtained by the DFT simulations and the SCXRD experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To unravel the links between the idealistic situation of an ion pair or a small cluster and the real crystalline material at room temperature, the DFT calculations were compared with experimental data from the solid. For this purpose, the geometries of the ion pair and its dimer were deduced from Single Crystal X‐ray diffraction (SCXRD) measurements reported on the Cambridge Crystallographic Data Centre (CCDC, entry number 1550837) . Table compares selected geometric parameters obtained by the DFT simulations and the SCXRD experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids (ILs) are fascinating ionic materials that have attracted considerable attention in various fields in recent years. This includes organic synthesis and catalysis, electrochemistry, chemical sensing,, and dye‐sensitized solar cells, but also their potential use as energetic materials,, lubricants, and electro‐wetting agents, has sparked an interest in academia and industry. Their attractive and potentially tunable properties make them not just replacements for conventional solvents but open up opportunities to use them as new platforms for advanced multi‐purpose materials, for example by combining them with nanostructured materials …”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, the introduction of the nitrooxy group in side chains or the methyl group on C‐2 has an opposite effect on the energetic properties of 2 and 4 a‐f . The detonation velocities and detonation pressures of energetic salts 2 and 4 a‐f with an 1,2‐dimethyl‐3‐(2‐nitrooxyethyl)imidazolium cation are much higher than those of energetic salts with an 1,2‐dimethyl‐3‐(2‐hydroxyethyl)imidazolium cation, but slightly lower than those of energetic salts with an 1‐methyl‐3‐(2‐nitrooxyethyl)imidazolium cation, when their anions are the same. This shows that the introduction of nitrooxy energetic group into the cation can improve their energetic properties.…”
Section: Resultsmentioning
confidence: 88%
“…The decomposition temperatures of the salts are given in Table . Comparatively, the decomposition temperatures of 2 and 4 a‐f with an 1,2‐dimethyl‐3‐(2‐nitrooxyethyl)imidazolium cation are generally lower than those of energetic salts with an 1,2‐dimethyl‐3‐(2‐hydroxyethyl)imidazolium cation, but higher than those of energetic salts with an 1‐methyl‐3‐(2‐nitrooxyethyl)imidazolium cation, when their anions are the same. This shows that the introduction of the nitrooxy group in side chains or the methyl group on C‐2 has an opposite effect on their thermo‐stabilities.…”
Section: Resultsmentioning
confidence: 91%
“…Solid-state crystal structure analysis is very useful in determining the dependence on intermolecular forces and predicting volumetric heat expansion. Yet, studies have shown that the inherent intermolecular organization of imidazolium-based ILs alter the crystal state by forming either triclinic (for RTILs containing oxygen and/or high attractive forces) or monoclinic (weak attractive interactions) [ 35 ]. Furthermore, identifying key features of crystal structures can be very useful in predicting heat expansion trends.…”
Section: Results and Analysismentioning
confidence: 99%